Pengujian Kualitas Air Kemasan Minieral dengan Pengukuran Indeks Biasa Air Menggunakan Metode Difraksi Fraunhofer - Tisar Dewi Pratiwi; Radhitya Perdhana; Mitranikasih Laia; Rohmawati Metaningrum (Jurnal Teori dan Aplikasi Fisika, 2024)
On a laboratory scale, water quality measurements generally use the degree of acidity (pH) and wather index. This study aims to implement simple physics equations with the tools we make by applying the principle of light diffraction. One of the parameters to determine the level of water quality can be through the measurement of the water index. We use the single-slit Fraunhofer diffraction method to measure the water index in mineral bottled water, including Tripanca, Grand and Aqua. Then the results are compared with the results of measuring the water index in turbid water. The results we obtained showed that Tripanca bottled water was 1.34 ± 0.16, Grand was 1.36 ± 0.39 and Aqua was 1.32 ± 0.51. Turbid water measurements get a water index value of 1.62 ± 0.003. When compared with the laboratory water index value of 1.33, the average bottled water has a water index that is lower than the laboratory water index, and turbid water has a water index that is greater than the laboratory water index. This is because the greater the value of the refractive index of water, it will inhibit light from entering the water medium, thereby reducing the quality of the water.   Keywords: Light diffraction, Refractive index of water, Water Mineral Content, Linear regression.